Transformers : creative teachers for the 21st century - Schreck, Mary Kim (NU Curriculum., 2009)
Packed with research-based strategies, this step-by-step resource shows educators how to cultivate a more creative teaching practice by accessing their creative resources, eliciting students' creativity, and more.